Analysis of factors influencing accuracy of ultrasound-based fetal weight estimation - Hiwale, Sujitkumar; Firtion, Celine (Indian Journal of Radiology and Imaging, 2020)
Context: The primary objective of this study was to examine the impact of maternal age, parity, gestational age, fetal gender, gestational diabetes mellitus, and pregnancy-induced hypertension on the accuracy of ultrasonography-based fetal weight estimation. The secondary objective was to find the impact of a formula selection on the accuracy of fetal weight estimation. Subjects and Methods: The inclusion criteria were a live-birth singleton pregnancy and the last ultrasound scan to delivery interval ≤7 days. Fetal weight was estimated using the Hadlock-4 formula. To study the concurrent impact of all the factors on the accuracy, cases were divided into two subcategories based on percentage error, with ±10% as a threshold. The accuracy of Hadlock-4 formula was compared with the two Indian population-based formulas, Hiwale-1 and Hiwale-2. Results: In total, 184 cases were included in the study. It was observed that the systematic error in weight estimation was significantly less in the male fetuses (8.45 ± 9.34%) in comparison to the female fetuses (11.71 ± 10.34%). The combined impact of all the factors on the accuracy was found to be nonsignificant by the multivariate analysis. The Hiwale-1 (-0.59 ± 8.75%) and Hiwale-2 (-0.65 ± 8.7%) formulas had statistically significant less errors compared to the Hadlock-4 formula (11.67 ± 7.95%). Conclusion: All the studied clinical factors were found to have a limited impact on the overall accuracy of fetal weight estimation. However, the formula selection was found to have a significant impact on the accuracy, with the native population-based formulas being significantly more accurate.
Keywords: Factors affecting accuracy; fetal ultrasonography; fetal weight; India; multivariate analysis